CCL3 correlates with ferroptosis in intervertebral disc degeneration and its prognostic significance - He Chen; Peng Xu; Leijing Mao; Yicong Wang; Zian Feng; Zhongxin Wang; Cailiang Shen; Yuanhong Xu (Scientific Reports)
Abstract Intervertebral disc degeneration (IVDD) is a prevalent and debilitating condition associated with low back pain (LBP). Despite its significant impact, effective diagnostic markers for early-stage IVDD remain elusive. Recent research has implicated ferroptosis, a newly recognized form of programmed cell death, in the pathogenesis of IVDD, particularly involving disturbances in iron homeostasis. Additionally, the CC Chemokine Ligand 3 (CCL3) has been linked to macrophage migration and the progression of IVDD, yet its precise diagnostic and prognostic utility remains uncertain. This study aims to elucidate the underlying mechanisms of ferroptosis and the involvement of CCL3 in IVDD, with the objective of establishing their diagnostic and prognostic significance. By uncovering these mechanisms, novel biomarkers and therapeutic targets for the diagnosis and prognosis of IVDD may be identified. Single-cell sequencing data were acquired from the TCGA database, and a range of bioinformatics methods were employed for comprehensive analysis. Furthermore, validation experiments were conducted using in vitro techniques, including the analysis of human tissue samples, co-culture assays with neutralizing antibodies, quantitative real-time polymerase chain reaction (qRT-PCR), and Western blotting. Our findings suggest that CCL3 holds promise as a diagnostic and may was prognostic biomarker for IVDD. Validation experiments demonstrated that CCL3 functions via the pAMPK/AMPK pathway, thereby modulating apoptosis and impacting the progression of IVDD. Our study underscores the diagnostic and prognostic potential of CCL3 in patients with IVDD. Further investigations are warranted to explore therapeutic strategies targeting CCL3, ultimately enhancing the management of IVDD.